Digital Mechanization and Administrative Decision-Making - Ekhlas Abarahim Khalf Ebrahim Alzubaydi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Public administration is undergoing rapid transformation through digital mechanization, shifting from paper-based processes to electronic systems for data collection, processing, and decision-making. Specific Background: This transformation has altered the formation, issuance, and implementation of administrative decisions within a technological environment where legal principles intersect with digital systems. Knowledge Gap: Despite increasing reliance on automated systems, existing Iraqi legislation lacks explicit regulation of electronic administrative decisions and their legal implications. Aims: This study aims to analyze the legal foundations of digital mechanization, examine its effects on the elements of administrative decisions, and assess the adequacy of the Iraqi legislative framework in governing automated decision-making. Results: The findings indicate that digital mechanization restructures administrative decisions by integrating data-driven processes, modifies elements such as competence, form, and subject matter, and introduces electronic notification and publication mechanisms. However, legal responsibility remains attributed to administrative authorities, while risks to rights and freedoms persist due to algorithmic errors and insufficient legal safeguards. Novelty: The study provides a comprehensive legal analysis linking digital mechanization with traditional administrative law principles within the Iraqi context. Implications: The results highlight the necessity of a clear legislative framework to regulate electronic administrative decisions, ensure accountability, and balance technological development with the protection of legality and individual rights. Highlights:• Identifies Structural Transformation of Decision Processes Through Automated Data Systems• Demonstrates Persistence of Institutional Liability Despite Algorithmic Involvement• Reveals Regulatory Gaps in Governing Electronic Procedures and Legal Safeguards Keywords: Digital Mechanization, Administrative Decision Making, Electronic Administrative Decision, Legal Responsibility, Iraqi Administrative Law